Silent Way Method Sebagai Alternatif Pembelajaran Maharatul Istima’ - Isnawati Malik; Hairuddin; Mukhtar I. Miolo; Musdelifa Abu Samad (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2023)
This study examines the application of the Silent Way method (At-Thariqah Al-Shamitah) in Arabic language learning, with a focus on enhancing students' maharatul istima’ (listening skills). The Silent Way method, which emphasizes the active role of students in the learning process and limits teacher intervention, is used to improve listening skills through Arabic language instruction. This research employs a Classroom Action Research (CAR) approach consisting of three cycles: planning, implementation, observation, and reflection. In each cycle, the teacher applies Silent Way strategies, observes student progress, and makes continuous improvements based on observation results. The study results show that the application of the Silent Way method significantly improves students' listening abilities in Arabic language learning. Data were obtained from pre- and post-cycle tests, classroom observations, and student feedback. Data analysis indicates an increase in the average maharatul istima’ scores and an improvement in student engagement and motivation in the learning process. The study concludes that the Silent Way method is effective in enhancing students' listening skills and recommends this method as an alternative strategy in Arabic language instruction.